(untitled) (Universal International Scientific Journal, 2026)
The article covers the essence of distance learning, didactic foundations, pedagogical principles, interactivity, individualization, differentiation, independent learning, reflection, and control. It also explains the role of electronic platforms, digital resources, video lessons, forums, testing systems, and virtual collaboration tools in organizing distance learning.